Effect Of Combination Therapy Of Insulin – Metformin On Life Quality Of Diabetes Mellitus Patient In Type 2 - Ramdhani M Natsir; Minarty M Natsir (Politeknik Kesehatan Makassar, 2021)
Diabetes mellitus type 2 is a metabolic disease that requires long-term therapy and can not be cured completely, resulting in the quality of life. Objective: The aims of the study to the effect of combination therapy of insulin – metformin on life quality of diabetes mellitus patient in type 2 endocrine polyclinic of Dr. Wahidin Sudirohusodo Hospital by using parameters of fasting blood glucose levels, blood glucose and A1C. Method: This study used a descriptive analysis design with cross sectional approach. The data is obtained concurrently with theinterviews and questionnaires and medical records of patients. Results: Based on the chi-square insulin–metformin combination therapy affect fasting blood glucose level (p value = 0.016) and A1C (p value = 0.026) significantly. Conclusion: The use of single insulin combination therapy with metformin (p value = 0.025) indicated improved quality of life.